Delivery outcome following previous caesarean birth in two different inter-delivery intervals : a comparative cross-sectional study - Norhayati binti Mohd Yusof (Kulliyyah of Medicine, International Islamic University Malaysia, 2015)
The aim of this study was to determine the success rate of VBAC in women with inter-delivery interval below and above 19 months, apart from comparing the maternal morbidity and the fetal outcome between the two groups. This is a cross-sectional study that was conducted in the Obstetrics & Gynaecological Department Hospital Tengku Ampuan Afzan, Kuantan Pahang from June 2013 until June 2015. The sample populations were women with singleton foetus with cephalic presentation and had one previous caesarean section. Those who had a vaginal birth after the previous caesarean section and those who were not suitable for VBAC were excluded from the study. The collected data were analyzed using IBM SPSS Statistics 20. Chi-square and Fisher exact tests were employed for categorical variables, and the Independent-samples t- test was used for continuous variables. Multivariate analysis was done using binary logistic regression to evaluate the association of VBAC success with inter-delivery interval and other potential confounding factors. A P value of < 0.05 was considered statistically significant. Of the 590 women, 300 of them were randomly chosen for analysis. Sixty of them were in the group A (inter-delivery interval of less or equal than 19 months) while 240 patients were in the group B (inter-delivery interval more than 19 months). In this study, the shorter the inter-delivery interval, the higher success rate of VBAC (78.3% versus 55% for group A and group B respectively). There was no difference in terms of maternal morbidities of the two groups. The rate of uterine rupture or dehiscence were also of no significant difference for both groups (0.0% versus 0.4%; p = 0.632). No significant perinatal outcome was also observed. As a conclusion, in our population, the VBAC success of inter-delivery interval of less than 19 months were comparable to the inter-delivery interval of more than 19 months with no significant association with maternal and neonatal morbidity. Therefore, these results may be helpful to obstetricians in term of counseling and recommending patients with short inter-delivery interval for a trial of vagina delivery after caesarean section. The aim to reduce caesarean section rates and its associated morbidity is possible to be achieved